Construction of 3D CoO Quantum Dots/Graphene Hydrogels as Binder-Free Electrodes for Ultra-high Rate Energy Storage Applications. (20th July 2017) - Wang, Ronghua; Han, Meng; Zhao, Qiannan; Ren, Zongling; Xu, Chaohe; Hu, Ning; Ning, Huiming; Song, Shufeng; Lee, Jong-Min
Abstract: We have developed binder-free electrode materials composed of CoO quantum dots on three-dimensional (3D) graphene hydrogels. The CoO quantum dots with size of only 3 ∼ 6 nm are uniformly decorated onto the surface of graphene, then as building blocks assembled to 3D structures during a solvothermal process. The designed electrode configuration takes advantage of ultra-small particle sizes, large surface area, 3D microstructures, and good electronic conductivities. These merits lead to the 3D CoO quantum dots/graphene hybrid hydrogels exhibiting specific capacitances of 889.7 ∼ 822 F g −1 at current densities of 2 to 50 A g −1, capacitance retention as high as 92.4%. The hybrid energy storage devices by using our hybrid hydrogels as positive electrodes and pure graphene hydrogels as negative electrodes can deliver an energy density of 28.7 and 23.0 Wh kg −1 at a power density of 1600 and 12000 W kg −1, and exhibit remarkable long-term stability with almost no capacitance loss at all even up to 5000 cycles, indicating that our designed 3D CoO quantum dots/graphene hybrid hydrogels would be one of the promising active materials for energy storage applications.